Bridges to Sobriety: Testing the Feasibility and Acceptability of a Mobile App Designed to Supplement an Adolescent Substance Use Disorder Treatment Program - Patterson Silver Wolf, David A.; Ramsey, Alex T.; Epstein, Joel; Beeler-Stinn, Sara; Asher Black Deer, Autumn (Clinical social work journal, 2022)
Adolescent substance use is a growing problem that causes a myriad of negative outcomes. Using substances during adolescence can lead to decreased executive functioning and is correlated with the top three causes of deaths for adolescents. Treatment options vary and the impact on outcomes are mixed, with engagement being of the most important indicators. Gaming is a popular activity among adolescents, and yet smartphone applications are relatively unexplored within substance use disorder treatment programs. This paper explores the feasibility and acceptability of implementing a mobile application as a supplement to existing adolescent substance use disorder treatment in a behavioral health agency in eastern Missouri. Feedback was received from staff and clients to assess feasibility and acceptability of implementation with barriers discussed. Results indicate there is promise with incorporation of smartphone-based applications into existing interventions and act as recommendations for other providers.